2015
DOI: 10.1007/12_2015_308
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystals of Cellulosics: Fascinating Ordered Structures for the Design of Functional Material Systems

Abstract: This article surveys progress in both fundamental and applied research related to cellulosic liquid crystals, mainly of chiral nematic order. These liquid crystals are divided into two different classes, namely cellulosic macromolecules and cellulose nanocrystals (CNCs), depending on the mesogenic constituent. We start with a review of the fundamental and chiroptical characteristics of molecular liquid crystals of representative cellulose derivatives and then discuss recent efforts on the design and constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 132 publications
(185 reference statements)
0
36
0
Order By: Relevance
“…The surface charge of CNC is primarily controlled by the hydrolysis conditions. Higher acid concentration, reaction time and temperature produces CNC of higher surface charge as promoted by sulphuric acid diffusion into fibers (Nishio et al, 2016 ). Zeta-potential of CNC produced by sulphuric acid hydrolysis varies from −20 to −80 mV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface charge of CNC is primarily controlled by the hydrolysis conditions. Higher acid concentration, reaction time and temperature produces CNC of higher surface charge as promoted by sulphuric acid diffusion into fibers (Nishio et al, 2016 ). Zeta-potential of CNC produced by sulphuric acid hydrolysis varies from −20 to −80 mV.…”
Section: Introductionmentioning
confidence: 99%
“…Zeta-potential of CNC produced by sulphuric acid hydrolysis varies from −20 to −80 mV. In contrast, if hydrochloric acid is used to produce CNC, the resulting CNC has almost no charge (Nishio et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulosic polymers can form a liquid crystalline phase in a condensed fluid state because of the inherent semirigidity in the carbohydrate backbone (Fukuda et al 1994;Fukuda et al 1995;Gray 1994;Gray and Harkness 1994;Guo and Gray 1994;Nishio et al 2016;Zugenmaier 1994;Zugenmaier 1998). The supramolecular arrangement in the mesophase is mostly chiral nematic (synonymous with cholesteric), probably originating from a chiral nature (asymmetry) in the molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…The supramolecular arrangement in the mesophase is mostly chiral nematic (synonymous with cholesteric), probably originating from a chiral nature (asymmetry) in the molecular structure. (Hydroxypropyl)cellulose (HPC) is a familiar liquid-crystalline cellulose derivative and offers the chiral nematics in a variety of common solvents (Gilbert and Patton 1983;Gray 1983Gray , 1985Gray , 1994Guo and Gray 1994;Nishio 2006;Nishio et al 2016;Zugenmaier 1998). This type of mesophase often imparts a vivid color due to selective light reflection, when the supramolecular helical periodicity (i.e., pitch P) is comparable to wavelengths of visible light.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the important properties and characteristics of nanocellulose can be tuned by varying the fabrication strategies and the sources of cellulose . Since the chiral nematic orientation of acid‐hydrolyzed CNC suspensions was first reported, the influences of various conditions such as addition field, ionic strength, counterions, preparation conditions, and reaction conditions on the anisotropic chiral nematic liquid crystal behaviors of suspensions were widely investigated . The phase separation phenomenon of CNC suspensions could be observed when its concentration exceeded a critical value.…”
Section: Introductionmentioning
confidence: 99%